1999
DOI: 10.1111/j.1468-2958.1999.tb00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Explanations for Sex Differences in Emotional Support A Test of the Different Cultures and Skill Specialization Accounts

Abstract: Abstract:Research documents sex differences in interpersonal behaviors, such as comforting and emotional support, with women consistently being more likely than men to engage in comforting behavior, to produce sophisticated comforting messages, to value comforting skills, and to select friends based on comforting skills. Explanations for these gender differences include the "different cultures account" and the "skill specialization account." This research was designed to test these explanations by assessing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
105
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 53 publications
14
105
1
1
Order By: Relevance
“…Consistent with these findings, considerable research indicates that women discriminate more sharply than do men between better and worse efforts to provide emotional support. Specifically, US college women evaluate sophisticated, sensitive support efforts as more helpful than do men and further evaluate unsophisticated, insensitive support efforts as less helpful than do men (e.g., Kunkel and Burleson 1999). This particular gender difference has also been found in samples of US children, adolescents, and adults (Clark et al 2008;Jones and Burleson 1997;Servaty-Seib and Burleson 2007), as well as in multiple US ethnic groups (Samter et al 1997), and in samples of both sojourning and domestic Chinese Burleson and Mortenson 2003).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Consistent with these findings, considerable research indicates that women discriminate more sharply than do men between better and worse efforts to provide emotional support. Specifically, US college women evaluate sophisticated, sensitive support efforts as more helpful than do men and further evaluate unsophisticated, insensitive support efforts as less helpful than do men (e.g., Kunkel and Burleson 1999). This particular gender difference has also been found in samples of US children, adolescents, and adults (Clark et al 2008;Jones and Burleson 1997;Servaty-Seib and Burleson 2007), as well as in multiple US ethnic groups (Samter et al 1997), and in samples of both sojourning and domestic Chinese Burleson and Mortenson 2003).…”
Section: Introductionmentioning
confidence: 87%
“…Given the effectiveness of HPC messages, it is important to underscore that both men and women evaluate and respond more positively to HPC comforting messages than to LPC messages (see Burleson and Kunkel 2006); however, studies with US college students have also found that women respond somewhat more favorably to HPC messages than do men, whereas men respond somewhat more favorably to LPC messages than do women (e.g., Kunkel and Burleson 1999;MacGeorge et al 2004). As noted previously, there is evidence that this pattern of gender differences in responses to supportive messages is widespread, existing in multiple American ethnic groups (Samter et al 1997), as well as other cultures, such as China (Burleson and Mortenson 2003).…”
Section: Gender Differences and Supportive Communicationmentioning
confidence: 95%
“…Overall, similar others commonly make the best support providers (Thoits, 1995), and women often approach other women as sources of support (Kunkel & Burleson, 1999). Given the tension, uncertainty, and lack of success that can accompany interactions across racial lines, we expect that women gravitate toward members of their own race for support because these individuals best understand their plight and circumstances (Davis, 2015;Hecht et al, 2003).…”
Section: Support Gaps According To the Racial Composition Of A Dyadmentioning
confidence: 99%
“…Race and gender are salient source characteristics that shape the way people engage in interpersonal interactions (e.g., Kunkel & Burleson, 1999;Omi & Winant, 2014). Generally, people affiliate with, trust, and favor people who share similar identities (Tajfel & Turner, 1979).…”
Section: Support Gaps According To the Racial Composition Of A Dyadmentioning
confidence: 99%
“…It has also been found in other contexts that women receive less spousal support than men (Cutrona, 1996;Glynn et al, 1999;Kunkel & Burleson, 1999;Pasch & Bradbury, 1998). Explanations for this may be that (a) men do indeed provide less support to their partners, (b) women do not benefit from support as much as men do, (c) men do not provide support as effectively as women do, or (d) men do not provide effective support in particular to women.…”
Section: Discussionmentioning
confidence: 95%